ALTERNATIF PENGGANTI PASTA ALUMINA SEBAGAI BAHAN POLISHER UNTUK METALOGRAFI - Ari Wibowo; Hanifah Widiastuti; Nurman Pamungkas; Cahyo Budi Nugroho (Politeknik Negeri Batam, 2020)
Polishing have played an important role in the preparation of metallography testing. Poor polishing produce in an unflat and rough surface of the material, resulting an unclear metallography image that is difficult to identified. In general, the material commonly used for polishing is alumina paste. Alumina paste is expensive and takes a few minutes to produce a smooth and flat surface. In this research, polishing was done by using several metal polisher other than alumina paste, these were magic***, auto***, bras**, ki*, menze*** and pri** which are sold cheaply at supermarkets or online stores. Analysis was carried out on the surface of the polishing by these materials and the etching surface. The test results showed that the material that is polished with magic *** has the smoothest surface or has the least residual scratches compared to other materials even compared to alumina paste, but has the disadvantage of corrosion forming on some parts of the surface. The best polishing time was obtained on polishing for 3 minutes